Engineering Application of DC 750 V Power Feedback Set for UMT Power System - JI Hongwei (Kongzhi Yu Xinxi Jishu)
Energy feedback solutions based on multiple 4-quarter PWM converter has become a main direction of the current energysaving technology for urban mass transit(UMT). This paper demonstrated the effectiveness and practicability of the system by introducing simulation and practical engineering application of this solution.